Answer:
Solution set: {(-9/2, -41/2)}
Explanation:
Given that:
8x = 2y + 5 -------- eq1
3x = y + 7 ---------- eq2
From eq2 we get:
y =3x -7 ------ eq3
Now putting this value of y in eq1 we get:
8x = 2(3x - 7) + 5
By simplifying we get:
8x = 6x - 14 + 5
8x = 6x -9
8x - 6x = -9
2x = -9
x = -9/2
Putting value of x in eq3
y =3(-9/2) -7
y = -27/2 -7
Taking LCM
y = -27/2 - 14/2
y = -41/2
Hence,
Solution set: {(-9/2, -41/2)}
Now substituting the values of x and y in eq1 and eq2:
8(-9/2) = 2(-41/2) + 5
-72/2 = -41 + 5
-36 = -36
Hence proved
3x = y + 7
3(-9/2) = (-41/2) + 7
-27/2 = -27/2
Hence proved
i hope it will help you!